Presurgical accuracy of dipole clustering in MRI-negative pediatric patients with epilepsy: Validation against intracranial EEG and resection. (September 2022) - Ntolkeras, Georgios; Tamilia, Eleonora; AlHilani, Michel; Bolton, Jeffrey; Ellen Grant, P.; Prabhu, Sanjay P.; Madsen, Joseph R.; Stufflebeam, Steven M.; Pearl, Phillip L.; Papadelis, Christos
Highlights: Interictal magnetic and electric source imaging (MSI and ESI) using dipole clustering helps localizing the seizure onset zone (SOZ) and irritative zone (IZ) in MRI-negative patients with drug resistant epilepsy (DRE). Interictal MSI and ESI using dipole clustering facilitate the prognostic assessment of MRI-negative patients with DRE. Clustered dipoles show higher precision to the SOZ and IZ than scattered in MRI-negative patients with DRE. Abstract: Objective: To assess the utility of interictal magnetic and electric source imaging (MSI and ESI) using dipole clustering in magnetic resonance imaging (MRI)-negative patients with drug resistant epilepsy (DRE). Methods: We localized spikes in low-density (LD-EEG) and high-density (HD-EEG) electroencephalography as well as magnetoencephalography (MEG) recordings using dipoles from 11 pediatric patients. We computed each dipole's level of clustering and used it to discriminate between clustered and scattered dipoles. For each dipole, we computed the distance from seizure onset zone (SOZ) and irritative zone (IZ) defined by intracranial EEG. Finally, we assessed whether dipoles proximity to resection was predictive of outcome. Results: LD-EEG had lower clusterness compared to HD-EEG and MEG (p < 0.05). For all modalities, clustered dipoles showed higher proximity to SOZ and IZ than scattered (p < 0.001). Resection percentage was higher in optimal vs. suboptimal outcome patients (p < 0.001); their proximity to resection was correlated to outcome (p < 0.001). No difference in resection percentage was seen for scattered dipoles between groups. Conclusion: MSI and ESI dipole clustering helps to localize the SOZ and IZ and facilitate the prognostic assessment of MRI-negative patients with DRE. Significance: Assessing the MSI and ESI clustering allows recognizing epileptogenic areas whose removal is associated with optimal outcome.